Effect of Polyvinylpyrrolidone on biodegradable film derived from chitosan- Poly (Vinyl Alcohol) for plastic packaging application: article - Idris, Nurul Umirah; Subuki, Istikamah (2017)
Plastic waste disposal has become a very serious problem because of its high volume of solid waste and takes a very long period of times to decompose because it was made up from non-biodegradable synthetic polymer. Blending of natural polymer and synthetic polymer is one of the options to reduce the time of decomposition. Various study of blending of chitosan with PVA is conducted in the past to overcome this issue. It shows that the blended film of chitosan and PVA have good film forming properties. In this study, it covers the effects of addition of PVP into those blended film. PVP is synthetic polymer that also has good film forming properties. Plastic film is prepared by using different ratio of chitosan-PVA with addition of different concentration of PVP solution. The plastic films were subject to mechanical property testing using testing machine. It was found that the addition of PVP does improve the properties of the chitosan in terms of mechanical properties. Swelling test and FTIR Analysis was conducted to determine the chemical nature of film and to determine the functional group of the plastic films. The swelling test of plastic film was carried out to determine the degree of swelling of the plastic polymers